Outcome From a Randomized Controlled Clinical Trial ― Improvement of Peripheral Arterial Disease by Granulocyte Colony-Stimulating Factor-Mobilized Autologous Peripheral-Blood-Mononuclear Cell Transplantation (IMPACT) - Horie, Takashi; Yamazaki, Seiji; Hanada, Sayaka; Kobayashi, Shuzo; Tsukamoto, Tatsuo; Haruna, Tetsuya; Sakaguchi, Katsuhiko; Sakai, Ken; Obara, Hideaki; Morishita, Kiyofumi; Saigo, Kenichi; Shintani, Yoshiaki; et al. (Circulation Journal, 2018)
Background:The clinical usefulness of peripheral blood (PB) mononuclear cell (MNC) transplantation in patients with peripheral arterial disease (PAD), especially in those with mild-to-moderate severity, has not been fully clarified.Methods and Results:A randomized clinical trial was conducted to evaluate the efficacy and safety of granulocyte colony-stimulating factor (G-CSF)-mobilized PBMNC transplantation in patients with PAD (Fontaine stage II–IV and Rutherford category 1–5) caused by arteriosclerosis obliterans or Buerger’s disease. The primary endpoint was progression-free survival (PFS). In total, 107 subjects were enrolled. At baseline, Fontaine stage was II/III in 82 patients and IV in 21, and 54 patients were on hemodialysis. A total of 50 patients had intramuscular transplantation of PBMNC combined with standard of care (SOC) (cell therapy group), and 53 received SOC only (control group). PFS tended to be improved in the cell therapy group than in the control group (P=0.07). PFS in Fontaine stage II/III subgroup was significantly better in the cell therapy group than in the control group. Cell therapy-related adverse events were transient and not serious.Conclusions:In this first randomized, large-scale clinical trial of G-CSF-mobilized PBMNC transplantation, the cell therapy was tolerated by a variety of PAD patients. The PBMNC therapy was significantly effective for inhibiting disease progression in mild-to-moderate PAD.